NATASHA’S HIERARCHY OF NEEDS IN NICOLA YOON’S THE SUN IS ALSO A STAR - Nadira Ayu Ninggar; Frans Sayogie (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research aims to show one of the main characters’ hierarchies of needs in The Sun is Also a Star by Nicola Yoon, which arises when Natasha, an undocumented immigrant who is about to be deported, tries to fulfill some of her needs before and after her deportation. In this research, the researchers used the hierarchy of needs theory by Abraham Maslow. The data of this research is collected by reading and marking some texts from the novel. Based on the analysis, the researchers find that Natasha can fulfill all of her needs, before and after the deportation, based on the five stages of the hierarchy of needs by Abraham Maslow. So, the result is even though she has to try hard in meeting her safety needs because, as an undocumented immigrant who is about to be deported, she feels worried to move back to Jamaica, and there are also some obstacles, but Natasha is still able to fulfill those needs when she arrived and started her new life in Jamaica, and finally she can reach her self-actualization. Based on Natasha’s motivation in meeting her needs, the researchers conclude that the most dominant needs that Natasha tries to fulfill are safety and love and belonging needs.